Performance and microbial community variations in thermophilic anaerobic digesters treating OTC medicated cow manure under different operational conditions. (April 2016) - Akyol, Çağrı; Turker, Gokhan; Ince, Orhan; Ertekin, Emine; Üstüner, Oya; Ince, Bahar
Highlights: Initial concentration of 2 mg/L OTC caused 10–30% inhibition on biogas yields. Higher inhibition was observed as mixing rate increased. OTC half-life was calculated between 13 and 19 days. Effect of OTC was more pronounced on microbial diversity than operational conditions. Methanogenesis was mostly through H2 and CO2 utilization. Abstract: This study aimed to determine the fate and effect of oxytetracycline (OTC) and its metabolites during thermophilic anaerobic digestion of cow manure. OTC-medicated and non-medicated digesters were operated at 55 °C with different volatile solids (VS) concentrations (4% and 6%) and mixing rates (90 and 120 rpm). OTC and its metabolites were measured by HPLC and LC/MS/MS, respectively. Microbial community dynamics were monitored by denaturing gradient gel electrophoresis (DGGE) and real-time PCR (qPCR). Approximately 2 mg/L initial OTC concentration caused 10–30% inhibition on biogas production and higher inhibition was observed as mixing rate increased. DGGE results indicated that OTC caused a shift in bacterial community structure and several species became dominant with time. Archaeal community decreased throughout the digestion period. RNA based qPCR analyses showed that gene copy numbers of bacteria and Methanomicrobiales declined in all digesters whereas gene copy numbers of Methanobacteriales and Methanosarcinales increased in high mixing rate digesters.